Investigating carbon footprints of the Malawi University of Science and Technology - Maulana, Precious Douglas; Chamdimba, Hope Baxter Nqcube; Mkandawire, Malazi; Chagunda, Mapereka Francis (Interaction, Community Engagement, and Social Environment, 2024)
Background: Increasing greenhouse gasses concentration in the atmosphere is perturbing the environment to cause grievous global warming and associated consequences. Following the rule that only measurable is manageable, mensuration of greenhouse gas intensiveness of different products, bodies, and processes is going on worldwide, expressed as their carbon footprints (CF). Methods: The methodologies for carbon footprint calculations are still evolving and it is emerging as an important tool for greenhouse gas management. The purpose of this paper was to determine the CF of the Malawi University of Science and Technology (MUST) campus and identify the stressors. The greenhouse gasses (GHG) protocol separates emissions into three scopes which include scope 1 of direct emissions, scope 2 which is indirect emissions, and scope 3 of other indirect emissions. Findings: The estimation of CF from transportation measured 930670.2 kgCO2e, and from electricity measured 2824243.2 kgCO2e while from the use of charcoal fuel measured 30804 kgCO2e. Results showed that emissions generated by gen-sets and transportation produced the highest contribution of 669124.8 kgCO2e and 238991.4 kgCO2e respectively to the MUST campus in the year 2018-2019 as compared to previous years (2015-2017). Conclusion: The study strongly suggested that for the whole 5 years period the use of gen-sets in the campus was the main stressor and this was due to frequent blackouts. Second was transport and as the university grows, the demand for transportation will also increase hence more emissions from transport. Therefore the study recommends that the university should be more considerate of these carbon dioxide sources so as it is trying to meet its needs and demand from these activities, it should also consider reducing the carbon footprint of the campus. Novelty/Originality of this Study: In a pioneering effort for Malawian higher education institutions, this study quantifies the carbon footprint of the Malawi University of Science and Technology campus, paving the way for targeted greenhouse gas management strategies in academic settings.